Implementasi Logika Fuzzy pada Kekuatan Sinyal yang Diterima Antena Viasat X-Band - Afif Nuur Hidayat; Bagus Fatkhurrozi; Ibrahim Nawawi (Institut Teknologi Dirgantara Adisutjipto, 2020)
The data that the antenna receives during satellite data acquisition has a signal strength that is affected by the antenna's movement at an elevation and azimuth angle. Every change in the two angles causes the signal strength received by the antenna to change. Signal strength calculation is important to be able to ensure satellite data is received well. Fuzzy Mamdani's logic as a method that can be used to calculate uncertain variables will be implemented in the calculation of the signal strength received by the Viasat X-Band antenna when the acquisition process of Aqua satellite data takes place. The results of the calculation of fuzzy mamdani logic by testing 6 signal strength data obtained from the Aqua satellite track analysis owned by LAPAN are shown in the percentage of errors, among others: DOY 197 of 1.33%; DOY 213 by 2.89%; DOY 259 of 1.93%; DOY 304 of 1.18%; DOY 320 by 4.73%; and DOY 357 of 2.27% and the average error (overall) of the entire data tested was 2.39%. This shows that the mamdani fuzzy logic is suitable for use in calculating the signal strength received by the Viasat X-Band antenna.